Control of sulphide during anaerobic treatment of S-containing wastewaters by adding limited amounts of oxygen or nitrate - Cirne, D. G. (2008)
Sulphide generated during anaerobic treatment of S-containing wastewaters represents an environmental problem. Adding limited amounts of oxygen or nitrate (or nitrite) to biologically (or chemically) oxidise sulphide forms a simple process level strategy to control this problem. This short review evaluates the feasibility and limitations of this strategy on the basis of the results of bioreactor studies.